Minibiotus weglarskae, a new species of Tardigrada (Eutardigrada: Macrobiotidae) from Mongolia - Michalczyk, Łukasz; Kaczmarek, Łukasz; Claxton, Sandra K. (Zootaxa, 2005)
A new eutardigrade, Minibiotus weglarskae sp. nov. is described from a lichen sample collected in Mongolia. This species is similar to Minibiotus bisoctus (Horning et al.) in having ten transverse bands of irregularly shaped pores around the body but differs from it by having a narrower buccal tube, much shorter macroplacoid row length and much shorter claws. The microplacoid of the new species is round and solid whilst that of M. bisoctus is lens-shaped and not solid.